2019
DOI: 10.4314/jasem.v23i2.17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dump site soil on the leaf structures of <i>Luffa cylindrical</i> (sponge gourd) and <i>Amaranthus viridis</i> (green amaranth)

Abstract: Previous researches have shown the presence of heavy metals (HMs) such as lead (Pb) at different levels in Olusosun dumpsite, Lagos. This study aimed at finding out if the anatomical differences found in Luffa cyclindrical and Amaranthus viridis grown on the dumpsite is an indication of the HMs and also determine the distribution of HMs on the dumpsite. The results showed the HMs detected in the dumpsite soil at three spots were significantly higher than the control (p=0.5). The concentrations of HMs were in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…Results from this study are in line with those reported by Ikhajiagbe and Anoliefo (2012), who suggested E. indica as a potential species for remediation of hydrocarbon pollution. However, the absence of significant changes in plant morphology even when exposed to organochlorine pesticide polluted soil disagrees with work presented by Ikhajiagbe et al, 2016 andMusa et al, 2019…”
Section: Morphology Of Eleusine Indica Tillerscontrasting
confidence: 80%
See 1 more Smart Citation
“…Results from this study are in line with those reported by Ikhajiagbe and Anoliefo (2012), who suggested E. indica as a potential species for remediation of hydrocarbon pollution. However, the absence of significant changes in plant morphology even when exposed to organochlorine pesticide polluted soil disagrees with work presented by Ikhajiagbe et al, 2016 andMusa et al, 2019…”
Section: Morphology Of Eleusine Indica Tillerscontrasting
confidence: 80%
“…Agricultural crops have also been reported to accumulate these pesticides and relay them into food chains and water bodies (Obida et al, 2012), which may likely cause harm to non-target organisms and thereby affect food security. Pesticides have also threatened the survival of less tolerance plant and animal species (Helfrich et al, 2009) causing necrosis and chlorosis of leaf structures (Musa et al, 2019) and human health complications (Lah, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Metal Pollution Index (MPI) was computed to analyse the heavy metal concentrations in the wastewater irrigated vegetables. This index obtained using the geometrical mean of concentrations of all the metals in the vegetables as described by (Ureso et al, 1997;Musa et al, 2019) following:…”
Section: Metal Pollution Index (Mpi)mentioning
confidence: 99%